Pulmonary AL amyloidosis and multiple myeloma presenting as cough with diffuse pulmonary opacities. Issue 7 (26th May 2021) - Xu, Alan; Lawton, Emily; Smith, Steven; Kalro, Akash; Geake, James
Abstract: Amyloidosis is an uncommon multisystem disease that can affect many organs. However, interstitial lung involvement is very rare. A 68‐year‐old man presented with long‐standing dyspnoea and productive cough. After extensive investigation, including two non‐diagnostic bronchoscopies, a surgical lung biopsy demonstrated pulmonary amyloidosis. A bone marrow biopsy confirmed multiple myeloma. The patient was treated with chemotherapy and an autologous stem cell transplant. Abstract : Interstitial pulmonary amyloidosis is very rare. A 68‐year‐old man presented with dyspnoea and cough, which demonstrated pulmonary amyloidosis after extensive investigation. Follow‐up bone marrow biopsy confirmed multiple myeloma.